Cell immunocapture microfluidic chip based on high-affinity recombinant protein binders - Smejkal, Jiří; Malý, Petr; Kuchař, Milan; Panova, Natalya; Semerádtová, Alena; Aubrecht, Petr; Štofik, Marcel; Malý, Jan (Biosensors & bioelectronics, 2021)
Cell immunocapture microfluidic devices represent a rapidly developing field with many potential applications in medical diagnostics. The core of such approach lies in the cell binding to antibody coated surfaces through their surface receptors. Here we show, that the small recombinant protein binders (PBs) can be used for this purpose as well, with the advantage of their constructional flexibility, possibility of fusion with range of tags and cheap mass production. For this purpose, two different PBs derived from Albumin Binding Domain (ABDwt) of streptococcal protein G, so called REX and ARS ligands with proved high affinity and selectivity to the human interleukin-23 (IL-23R) and IL-17 receptor A were used. Four PBs variants recognizing two different epitopes on two different receptors and two PBs variants binding to the same epitope on one receptor but having different peptide spacer with Avitag sequence necessary for their immobilization on sensor surface were tested for cell-capture efficiency. The glass microfluidic Y-system with planar immunocapture channel working in so-called stop-flow dynamic regime was designed. Up to 60-74% immunocapture efficiency of model THP-1 cells on REX/ARS surfaces and practically no cell binding on control ABDwt surfaces was achieved. Moreover, the specific immunocapture of THP-1 cells from mixture with IL-17RA negative DU-145 cells was demonstrated. We discuss the role of the epitope, affinity and immobilization spacer of PBs as well as the influence of stop-flow dynamic regime on the effectivity of THP-1 cell immunocapture. Results can be further exploited in design of microfluidic devices for rare cells immunocapture.
Keywords: Albumin-binding domain; biosenzitivní techniky; Biosensing Techniques; Rare cell population; Humans; receptory interleukinu-17; Microfluidics; Receptors, Interleukin-17; lidé; nádorové cirkulující buňky; rekombinantní proteiny; Recombinant Proteins; Recombinant protein binders; Neoplastic Cells, Circulating; Cell immunocapture; mikrofluidika